Acetylenic scaffolding with subphthalocyanines – synthetic scope and elucidation of electronic interactions in dimeric structures. Issue 46 (11th October 2017) - Gotfredsen, Henrik; Broløs, Line; Holmstrøm, Thomas; Sørensen, Jacob; Viñas Muñoz, Alberto; Kilde, Martin Drøhse; Skov, Anders B.; Santella, Marco; Hammerich, Ole; Nielsen, Mogens Brøndsted
Abstract : Acetylenic building blocks of the subphthalocyanine chromophore have been developed and employed for acetylenic scaffolding at axial and peripheral positions. Abstract : Boron subphthalocyanines (SubPcs) are powerful chromophoric heterocycles that can be synthetically modified at both axial and peripheral positions. Acetylenic scaffolding offers the possibility of building large, unsaturated carbon-rich frameworks that can exhibit excellent electron-accepting properties, and when combined with SubPcs it presents a convenient method for preparing interesting chromophore–acceptor architectures. Here we present synthetic methodologies for the post-functionalization of the relatively sensitive SubPc chromophore via acetylenic coupling reactions. By gentle AlCl3 -mediated alkynylation at the axial boron position, we managed to anchor two SubPcs to the geminal positions of a tetraethynylethene (TEE) acceptor. Convenient conditions that allow for stepwise desilylations of trimethylsilyl (TMS) and triisopropylsilyl (TIPS) protected SubPc-decorated acetylenes using silver(i ) fluoride were developed. The resulting terminal alkynes were successfully used as coupling partners in metal-catalyzed couplings, providing access to larger acetylenic SubPc scaffolds and multiple chromophore systems. Moreover, conditions allowing for the conversion of a terminal alkyne into an iodoalkyne in the presence of SubPc were developed, and the product was subjected to cross-coupling reactions affording unsymmetrical 1, 3-butadiynes. The degree of interactions between two SubPc units as a function of the acetylenic bridge was studied by UV-Vis absorption spectroscopy and cyclic voltammetry. A TEE bridging unit was found to strongly influence the reductions and oxidations of the two SubPc units, while a more flexible bridge had no influence.